Crimes of state past and present : government-sponsored atrocities and international legal responses - Crowe, David M. ([S.l.] : Routledge, 2010)
War Crimes and acts of genocide are as old as history itself, but particularly during the 20th century. Yet what are war crimes and acts of genocide? And why did it take the world so long to define these crimes and develop legal institutions to bring to justice individuals and nations responsible such crimes? Part of the answer lies in the nature of the major wars fought in the 20th century and in the changing nature of warfare itself. This study looks at war crimes committed during the Second World War in the USSR, Yugoslavia, Germany, and efforts to bring the perpetrators to justice. This led to successful postwar efforts to define and outlaw such crimes and, more recently, the creation of two international courts to bring war criminals to justice. This did not prevent the commitment of war crimes and acts of genocide throughout the world, particularly in Asia and Africa. And while efforts to bring war criminals to justice has been enhanced by the work of these courts, the problems associated with civil wars, command responsibility, and other issues have created new challenges for the international legal community in terms of the successful adjudication of such crimes. This book was based on a special issue of Nationalities Papers.
Keywords: Crimes against humanity; Genocide; International crimes; Intervention (International law); Political crimes and offenses; State crimes; War crimes